2017
DOI: 10.1186/s12879-017-2886-7
|View full text |Cite
|
Sign up to set email alerts
|

Elizabethkingia miricola as an opportunistic oral pathogen associated with superinfectious complications in humoral immunodeficiency: a case report

Abstract: Background Elizabethkingia miricola is a rare Gram-negative bacterium found in water and clinical specimens. Typical culturing methods often misidentify Elizabethkingia spp. as Flavobacterium or Chryseobacterium. Although diagnosis is based on culturing samples taken from sterile sites, such as blood, a proper identification of this bacterium requires an expertise that goes beyond the capabilities of a typical clinical laboratory.Case presentationA 35-year-old woman diagnosed with common variable immunodeficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…E. miricola has been sporadically reported to cause pneumonia, bacteremia, urinary tract infection, and periodontitis since its first proposal as a new species in 2003 [60,61,62,63]. A retrospective South Korean study reported that the annual incidence of E. miricola increased from 0 to 0.22 per 1000 admissions from 2009–2016 [17].…”
Section: Epidemiology Clinical Characteristics and Outcomesmentioning
confidence: 99%
“…E. miricola has been sporadically reported to cause pneumonia, bacteremia, urinary tract infection, and periodontitis since its first proposal as a new species in 2003 [60,61,62,63]. A retrospective South Korean study reported that the annual incidence of E. miricola increased from 0 to 0.22 per 1000 admissions from 2009–2016 [17].…”
Section: Epidemiology Clinical Characteristics and Outcomesmentioning
confidence: 99%
“…The majority of Australian aquatic environment isolates from this study were E. miricola. E. miricola is known to cause sepsis, oral and urinary tract infections ( Green et al., 2008 ; Lin et al., 2019a ; Zdziarski et al., 2017 ) though reports of infection are less frequent than that for E. meningoseptica and E. anophelis . Environmental E. miricola from this study formed two distinct clades.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional-specific taxa comprised of metal-mobilizing Metallosphaera cuprina ( Liu et al, 2011 ), environmental extremes-resistant Halorubrum sp. BOL3-1 ( DasSarma et al, 2019 ), and human pathogenic bacteria such as Elizabethkingia miricola ( Zdziarski et al, 2017 ), and Mycolicibacterium smegmatis ( Yamada et al, 2018 ). Organic-specific taxa consisted of plant growth-promoting bacteria including N 2 -fixing bacteria [i.e., Mesorhizobium loti ( Shimoda et al, 2016 ) and Bradyrhizobium sp.…”
Section: Discussionmentioning
confidence: 99%